Relevansi Pemikiran Ki Hajar Dewantara dalam Toleransi Beragama di Indonesia - Omang Komarudin; Danuri Danuri; Umi Kulsum; Hermawati Hermawati (LPPM Institut Agama Islam Nahdlatul Ulama Kebumen, 2024)
This article explores the relevance of Ki Hajar Dewantara's thought in presenting a paradigm of religious tolerance in Indonesia. As a pioneer of Taman Siswa, Ki Hajar Dewantara brought important contributions to the discourse of tolerance and inclusiveness. This article aims to provide solid and contextual scientific insights into how Ki Hajar Dewantara's thoughts can continue to color and form the foundation of religious tolerance in Indonesia. The research methodology in this article is a narrative review of the literature, by explaining Ki Hajar Dewantara's thoughts that are relevant to religious tolerance. The results of this research are 1) Ki Hajar Dewantara's thoughts on religious tolerance are relevant in the face of contemporary social, cultural and educational dynamics. 2). The influence of Ki Hajar Dewantara's thoughts in the world of education has proven to have a positive impact, related to the integration of religious tolerance values in the formal and non-formal curriculum illustrates how Ki Hajar Dewantara's thoughts become the foundation for the transformation of education in Indonesia, and 3). Case studies and successful examples illustrate that Ki Hajar Dewantara's thought is not only a theoretical concept, but also a practical guide. The implementation of this thought at various levels of education provides clear evidence that religious tolerance can be realized through real and measurable efforts.